(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper analyses the banking marketing evolution due to influence of information and communication technologies (ICT). These new technologies have represented the main tool for changing marketing paradigm from marketing-mix to anew based in relational networks. It describes the quintessential role played by ICT in fulfilling banks’ marketing objective of servicing customers better at less cost and there by reaping more profits, offering their customers a variety of products, lower prices, and personalized service. It also highlights how new technologies permit the use of strategies of customer relationship management and data mining in makinglong-lasting and profitable relationships with customers.